Pengembangan Pendidikan Informal - Made Pidarta (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
The informal education has not yet been developed as much as the formal and non formal education. This education plays an important role in developing children’s and youths personalities. Most of the time spent in their life is in informal education, especially through television program, daily life relationship and communication in the community and their family life. Cooperation between the Educational Department and other institutions related to television programs, communities and families is urgently needed. In the autonomy system, these three kinds of educations should be handled by Dinas Pendidikan, Dewan Pendidikan, and the board of mass education in kabupaten/kota. So, these kinds of education can equally be developed. On the lowest level, the informal education must be managed by Komite Sekolah which collaborates with other community organizations.